The Comstocks of Cornell the definitive autobiography - Comstock, Anna Botsford, 1854-1930 (Comstock Publishing Associates, an imprint of Cornell University Press, 2020)
"This book is a historic restoration of the complete autobiographical manuscript (later heavily edited) of a prominent Cornellian couple, John Comstock and Anna Botsford Comstock, and their enduring legacy at Cornell University"--